A Case Report of Slug Ingestion Causing Eosinophilic Meningitis, Papilledema, and Pronounced Motor Weakness in a US Marine. Issue 1 (22nd August 2019) - Widder, Jared R; Fallah, Shamis; Mondzelewski, Todd J
Abstract: Angiostrongyliasis is the most common cause of eosinophilic meningitis worldwide and is primarily characterized by eosinophilic meningitis, meningoencephalitis, or myelitis. It is caused by ingestion of the nematode Angiostrongylus cantonensis, the rat lungworm (or apple snail). The most common route of infection is by ingestion of parts of the intermediate hosts like mollusks or food contaminated with infective third stage larvae. Following ingestion, the larvae migrate through the intestinal walls into the bloodstream and further into the central nervous system where they cause meningo-encephalo-myelitis and can have a variety of ocular manifestations. We present a case of a Caucasian United States Marine who suffered severe meningo-encephalo-myelitis with papilledema following ingestion of a raw Giant African Snail ( Lissachatina lutica ) while stationed in Japan. He developed eosinophilic meningoencephalitis, polyneuropathy, motor weakness, and papilledema. We describe the unique clinical features of this disease in our patient.